Comparative experience of socio-pedagogical work with gifted children in the Russian Federation and Kazakhstan - Shcherbinina, O.S. (2021)
The authors conduct a comparative analysis of the features and content of socio-pedagogical work with gifted schoolchildren in the educational space of Russia and Kazakhstan. The purpose of our study: to study and present the comparative experience of socio-pedagogical work with gifted children in the Russian Federation and Kazakhstan. Collection of empirical data was carried out by questionnaire survey of teachers of general educational organizations of the Russian Federation (n=225) and educational organizations of Kazakhstan (n=200). The survey of teachers and specialists of educational organizations was conducted in 2018 and 2019.The authors have studied the comparative experience of organizing socio-pedagogical work with gifted schoolchildren in Russia and Kazakhstan. The results allow us to see common and specific in the work with gifted children in the Russian Federation and the former post-Soviet republic. The identified features can be taken into account in the organization of socio-pedagogical work with gifted schoolchildren and improve the effectiveness of socio-pedagogical work and socio-pedagogical support of gifted schoolchildren. In conclusion, the study of comparative experience of socio-pedagogical work with gifted schoolchildren in two countries with a similar history of formation of educational systems allows us to see the difference in approaches to work with this non-standard category of children at the moment. The identified specificity in the programs, forms and methods, target benchmarks of socio-pedagogical work with gifted children in educational organizations can be taken into account when developing the content of this direction of work and will improve its effectiveness.